Thermal Transitions of Pulp and Cuticle of Blueberries - Matiacevich, S; Enrione, J (2011)
The thermal transitions of two blueberries cultivars (Duke and Briggitte) were studied by differential scanning calorimetry as part of comprehensive study of blueberry conservation. Thermal transitions and texture (hardness) were determined in fresh and frozen fruits freezed at 5 °C/min and 40 °C/min. Glass transition temperatures were successfully detected in pulp and cuticle, which was associated to the soluble sugar fraction present in the fruit. Transitions associated to water crystallization and melting showed differences between both cultivars, which were explained by their soluble solids concentration. An endothermic transition at 50 °C was associated to the melting of epicuticular wax present in the cuticles. The cuticle was less affected by ice formation, which is an important feature to fruit protection at low temperatures. Hardness showed that cooling rate had not a significant effect on this quality parameter. Despite the complexity in the structure of blueberries, thermal characterization by DSC was successful. © 2011 Elsevier B.V.